Acute cerebral edema: a lethal neurological complication in a patient with COVID-19 infection. Case report and literature review - M. Puodžiūnaitė; R. Sadeckaitė; A. Čikotienė (Neurologijos seminarai)
Introduction. COVID-19 can damage the nervous system by direct viral damage to the neural cells or by immunopathology. More serious medical conditions such as cerebral edema, neuronal degeneration, encephalitis, acute disseminated encephalomyelitis, Guillain-Barre syndrome, Bickerstaff’s brainstem encephalitis, Miller-Fisher syndrome, polyneuritis, toxic encephalopathy, and stroke can occur. Case report. We report a case of a 40-year-old patient with previous history of hypertension and no other chronic disease who was admitted to the hospital with respiratory distress due to SARS-CoV-2-induced bilateral pneumonia. A few days later, he developed worsening respiratory function with an acute seizure episode. Head CT scan revealed subarachnoid hemorrhage with diffuse cerebral edema as a lethal neurological complication, possibly secondary to COVID-19. Discussion. COVID-19 induces CNS damage through various mechanisms including ACE-2 receptor damage, cytokine storm syndrome, secondary hypoxia, blood-brain barrier disruption, and neuroinflammation. Neurological symptoms correlate with the severity of COVID-19 disease and may range from asymptomatic infection to severe and lethal forms. Acute cerebral edema, as illustrated by our case, may result from a combination of diffuse en dothelial dysfunction, cytokine release syndrome, and hypoxic damage from pulmonary dysfunction.